Replication Data for "The Impact of Reducing Dietary Aflatoxin Exposure on Child Linear Growth: A Cluster Randomized Controlled Trial in Kenya" - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This dataset is produced from the randomized controlled trial (RCT), which was conducted to test for a causal impact of aflatoxin exposure on child growth. Participants were recruited from among households containing women in the last 5 months of pregnancy in 28 maize-growing villages within Meru and Tharaka-Nithi Counties in Kenya. Households in villages assigned to the intervention group are offered rapid testing of their stored maize for the presence of aflatoxin each month; any maize found to contain more than 10 ppb aflatoxin is replaced with an equal amount of maize that contains less than this concentration of the toxin. They are also offered the opportunity to buy maize that has been tested and found to contain less than 10 ppb aflatoxin at local shops. Clusters (villages) were allocated to the intervention group (28 villages containing 687 participating households) or control group (28 villages containing 536 participating households) using a random number generator. Data collection at baseline and follow-up were done at participants’ homes through face-to-face interviews. A pre-coded survey was administered to the expectant mother immediately after enrollment, her height and weight were measured, and self-reported month of pregnancy was recorded. Expectant mothers were also asked to provide a venous blood sample to be analyzed for serum aflatoxin. A similar survey was repeated during follow-up data collection at 24 months after enrollment. Participants enrolled in the fourth through sixth waves were additionally followed-up 24 months after the third enrollment wave. At each follow-up visit, the length and weight of the child in utero at baseline (reference child) were recorded, and a venous blood sample was taken from this child for serum aflatoxin analysis.